ANTIMICROBIAL ACTIVITY AND WOUND HEALING EVALUATION OF SILVER NANOPARTICLES SYNTHESIZED USING LEMON FRUIT PEEL EXTRACT (CITRUS X LIMON (L.) OSBECK) - Handiwidjaja, Adeline
The increasing consumption of drug compounds in the era of globalization has driven innovation in the pharmaceutical industry. One compound that is often a significant topic in the pharmaceutical industry is nanoparticles. One type of nanoparticle that has potential as an antimicrobial agent and assists in wound healing is silver nanoparticles. Silver nanoparticles can be synthesized through chemical, physical, and biological methods. However, chemical and physical methods have drawbacks concerning environmental pollution and stability issues. Therefore, the synthesis of silver nanoparticles using biological methods can be a solution to these problems. The aim of this research is to test the antimicrobial activity and wound healing properties of biologically synthesized silver nanoparticles. In this study, waste from lemon fruit peels (Citrus × limon (L.) Osbeck) was used as a bioreducer source in the green synthesis of silver nanoparticles. Subsequently, the silver nanoparticles were characterized and tested for antimicrobial activity and wound healing on a Swiss Webster mouse model. The characterization results indicated that the biologically synthesized silver nanoparticles had a Surface Plasmon Resonance at a wavelength of 420 nm and a size of 62.9 nm with a polydispersity index of 0.300. The antimicrobial activity test results showed that the biologically synthesized silver nanoparticles with lemon peel extract exhibited strong antimicrobial activity against Malassezia furfur, strong activity against Pseudomonas aeruginosa and Cutibacterium acnes, and moderate activity against Staphylococcus aureus with minimum inhibitory concentrations of 8, 16, 16, and 64 ppm, respectively. The wound healing activity test results revealed that the biologically synthesized silver nanoparticles with lemon peel extract exhibited wound healing activity with a wound closure percentage of 100% on the 9th day. Based on the overall research findings, it can be concluded that biologically synthesized silver nanoparticles with lemon peel extract exhibit good antimicrobial activity against Gramnegative bacteria, Gram-positive bacteria, and fungi, as well as wound healing activity.